THE NURSE'S ROLE IN COMMUNICATION WITH THE PATIENT/CLIENT - Tushe, Mirela (Nurse and Holistic Care, 2024)
The nurse plays a vital role in communication with the patient/ client. She/he is the person who spends the most time with the patient and constantly takes care of him/ her. From the first moments of presentation, reception and companionship of the patient, a relationship of interaction is created between each other. The nurse is the health professional who in the communication process is the information provider and the patient/client are the receiver, still these roles are sometimes exchanged depending on the situation. The way we communicate, the ethics we use, the behavior and attitude we maintain, the values ​​we present, show and highlight the figure and model of the professional nurse.